A HISTORY BEYOND "BELIEF". - Best, Wallace (Fides et historia, 2012)
The author reflects on the impact of religion on the history of African Americans, including their life and culture, in the U.S. The author emphasizes the importance of understanding the complexity of the manners in which religion has affected African American history. The author explores the lack of recognition of the historiography of both the non-religious and anti-religious African American population, while asserting that their history has been largely ignored. The author discusses the influence of the Harlem Renaissance and the writings of blacks between 1920 and 1940 on the role of non-religious beliefs and dissent among African Americans in the U.S.